O gênero discursivo meme – das origens à liquidez: um recorte conceitual e analítico para o estudo e ensino de Língua Portuguesa em sala de aula - Thiago Robson dos Santos (2021)
The first part of this dissertation presents a project of teaching and intervention carried out before the Covid-19 pandemic context. It is focused on the use of memes in a classroom of nine graders of a public school - a cycle of workshops under the Bakhtinian concept of discourse genres. This first planning, which was previous to the pandemic reality, has become a pilot plan of workshops- a pedagogical agenda of suggestions of activities for colleague teachers. Throughout these plannings, this work presents, in a concise way, basic concepts related to literacy, multi-literacies, multimodality, among other relevant topics necessary to study meme as a discourse genre. The second part of this dissertation presents reflections about the research process and the social effects caused by the pandemic period. Moreover, this work highlights a conceptual and analytical framework about the origins of the term meme, current ideas about Discursive Liquidity related to the metaphor of a liquid society under Bauman´s perspective and Rossana Furtado´s construct ( 2019) The goal of this work is to contribute to a better understanding of memes, as far as conceptual and historical frames are concerned, to present a synthesis of the most recent approaches on the meme genre, and finally to suggest classroom activities that can be developed within the teaching of Portuguese Language context.